Carbonic anhydrase VI: a novel marker for salivary serous acinar differentiation and its application to discriminate acinic cell carcinoma from mammary analogue secretory carcinoma of the salivary gland. Issue 5 (28th September 2015) - Hsieh, Min‐Shu; Jeng, Yung‐Ming; Jhuang, Yu‐Lin; Chou, Yueh‐Hung; Lin, Chiao‐Ying
Abstract : Aims: Carbonic anhydrase VI (CA6) is present in serous acinar cells of human salivary glands. The aim of this study was to investigate the diagnostic utility of CA6 in differentiating acinic cell carcinoma (AciCC) from its morphological mimic mammary analogue secretory carcinoma (MASC) of the salivary gland. Methods and results: CA6 immunostaining was performed in 28 cases of AciCC and 14 cases of MASC. All cases of AciCC showed positive CA6 staining. The staining pattern correlated with the number of serous acinar cells in tumours. All MASCs stained negatively for CA6. The results were compared with those obtained with currently used markers, including DOG1, mammaglobin, S100, and vimentin. CA6 showed sensitivity and specificity as high as those of DOG1 in diagnosing AciCC. CA6 expression was focally observed in basal cell adenoma and in one case of cystadenocarcinoma (1/3), but not in other salivary gland tumours, including mucoepidermoid carcinoma, adenoid cystic carcinoma, salivary duct carcinoma, lymphoepithelial carcinoma, epithelial–myoepithelial carcinoma, and pleomorphic adenoma. Conclusions: CA6 is a specific marker for serous acinar cells of salivary glands and AciCC. CA6 has sensitivity and specificity equal to those of DOG1 in the differential diagnosis between AciCC and MASC. A combination of CA6 and DOG1 could be an ideal immunohistochemical panel for AciCC.